Faktor-Faktor yang Mempengaruhi Kebijakan Dividen Pada Perusahaan Property dan Real Estate yang Terdaftar Di Bursa Efek Indonesia Periode 2014 – 2019 - Rahmadani, Rahmadani; Jefriyanto, Jefriyanto (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
The purpose of this study is to determine and analyze the factors that influence dividend policy simultaneously and partially in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The population in this study are companies listed in the property and real estate sector on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. The sample in this study used a purposive sampling technique, so from a population of 63 companies, 6 companies will be used as samples for 6 consecutive years, so that the total observations were 36 companies. The results of hypothesis testing prove that jointly firm size, liquidity, leverage, profitability, activity, cash flow, growth have a significant effect on dividend policy. Partially, company size has a negative and significant effect on dividend policy. Liquidity, profitability, and cash flow have a negative but insignificant effect on dividend policy. Leverage has a positive but not significant effect on dividend policy. Activity and Growth have a positive and significant effect on dividend policy. This research is expected to contribute to providing input and description regarding dividend policy so that it can help stakeholders.